What are the social constructs associated with the phrase "PM is the key" in digital marketing phenomenon / Mailyn Angca and JR Mantog - Angca, Mailyn; Mantog, JR (Universiti Teknologi MARA, 2024)
With the expeditious broadening of digital marketing, sending messages to the target market is highly unrestrained nowadays. This study utilized a qualitative phenomenological approach to explore on what online sellers ascribed to the phrase PM is the Key as commonly used phrase in digital marketing phenomenon. The data was gathered using in-depth interview. In addition, thematic analysis was utilized in analyzing the data. Results showed that the social constructs associated with PM is the key such as private inquiry, pricing, bait, strategy, and trend, are intended to stimulate consumer curiosity by giving essential information consumers consider while buying, such as product prices, by implying that they inquire privately. The online selling strategy is the most prevailing theme among generated social constructs. This study serves as a guide for potential online sellers and the basis for their online selling strategy.